2020
DOI: 10.1080/1028415x.2020.1769412
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase deficiency alters cellular response after ischemic stroke in male mice

Abstract: ObjectiveElevated homocysteine concentrations are a risk factor for stroke. A common genetic polymorphism in methylenetetrahydrofolate reductase (MTHFR 677 CT) results in elevated levels of homocysteine. MTHFR plays a critical role in the synthesis of S-adenosylmethionine (SAM), a global methyl donor. Our previous work has demonstrated that Mthfr +/mice, which model the MTHFR polymorphism in humans, are more vulnerable to ischemic damage. The aim of this study was to investigate the cellular mechanisms by whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Cellular ROS level is closely linked to various bone diseases and increased ROS level induced by RANKL has been reported to enhance osteoclastogenesis 28,29 . It is tightly regulated by Nrf2, which can promote the expression of antioxidant enzymes such as HO1and NQO1 30 . We found that the inhibition of MAT2A increased the expression of Nrf2, further affecting the ROS level.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Cellular ROS level is closely linked to various bone diseases and increased ROS level induced by RANKL has been reported to enhance osteoclastogenesis 28,29 . It is tightly regulated by Nrf2, which can promote the expression of antioxidant enzymes such as HO1and NQO1 30 . We found that the inhibition of MAT2A increased the expression of Nrf2, further affecting the ROS level.…”
Section: Discussionmentioning
confidence: 63%
“…28,29 It is tightly regulated by Nrf2, which can promote the expression of antioxidant enzymes such as HO1and NQO1. 30 We found that the inhibition of MAT2A increased the expression of Nrf2, further affecting the ROS level. Interestingly, combined with the results of a quasitargeted metabolomics assay, glutathione metabolism was also changed by sh RNA-MAT2A.…”
Section: Discussionmentioning
confidence: 72%
“…After mice were habituated to the Midwestern University animal facility, mice were randomly assigned to control or vitamin B12 deficient groups and placed on diets for 4 weeks. At 18 months of age, ischemic stroke was induced in animals using the photothrombosis model (Abato et al 2020; Jadavji et al 2018; Jadavji et al 2017; Labat-gest & Tomasi 2013; Lee et al 2004); this corresponds to middle-age in humans (Flurkey et al 2007). The ischemic stroke damaged the sensorimotor cortex, which allows for motor function assessment.…”
Section: Methodsmentioning
confidence: 99%
“…After mice were habituated to the Midwestern University animal facility, mice were randomly assigned to control or vitamin B12 deficient groups and placed on diets for 4 weeks. At 11 months of age, ischemic stroke was induced in animals using the photothrombosis model (Abato et al, 2020;Jadavji et al, 2018Jadavji et al, , 2017Labat-gest and Tomasi, 2013;Lee et al, 2004) this corresponds to middle aged in humans (Flurkey et al, 2007). The ischemic stroke damaged the sensorimotor cortex, which allows for motor function assessment.…”
Section: Experimental Designmentioning
confidence: 99%
“…Briefly, after mice were habituated to the Midwestern University animal facility for a period of one week, mice were randomly assigned to control or vitamin B12 deficient groups and placed on diets for 4 weeks. At 11 months of age, ischemic stroke was induced in animals using the photothrombosis model (10)(11)(12)(13)(14). The age of the mice corresponds to middle aged in humans (15).…”
Section: Experimental Designmentioning
confidence: 99%